Sustainable transformation in the Latin American and Caribbean districts through the implementation of a qualitative methodology. Challenges and key aspects to be addressed - Soutullo, Silvia (2024)
To mitigate the advance of rapid urbanization and the growing percentage of energy consumption in the countries of the Latin American and Caribbean region, it is necessary to transform these inhabited environments into efficient and sustainable areas. Energy consumption in this region has been mainly understood as an indicator of activity and development, often relegating the parameters of efficiency, environment and sustainability to the background. Therefore, it is necessary to adapt these criteria in the transformation processes of cities, considering energy efficiency, environment, energy accessibility, social inclusion and the green economy as key aspects. This requires governance models based on local factors that consider all the agents involved, enacting more sustainable and inclusive regulations and standards. This article presents a transformation methodology based on the analytical study of several districts in the Latin American and Caribbean region. This methodology enhances the ease implementation, provides great adaptability and replicability in different areas and contextual situations, and reduces reliance on information availability, focused instead on practically relevant and impactful solutions. It has been executed through the application of three matrices: SWOT, stakeholders and contextual factors, which allow for the identification of key barriers, driving factors and baseline situation. Applied to four real cases, this approach has resulted in the formulation of tailored improvement proposals for each case. The global analysis has identified environmental and sustainability issues, infrastructure and social aspects as the main challenges to be addressed, while the main gaps have been economic, infrastructure, mobility and governance issues. The design and execution of efficient solutions require central coordination, generally led by the local administration, which enhances the participation of the main actors and manages energy flows.